The Argument Scheme-based Approach to Argument Structure - Yu, Shiyang (Informal Logic, 2025)
The concept of argument structure is pivotal in argumentation theory and is extensively employed to analyze and describe arguments. However, as indicated in a previous study (Yu & Zenker, 2022), extant strength-based and relevance-based approaches fall short in distinguishing linked and convergent structures. This paper aims to address this gap by proposing a new argument scheme-based approach and demonstrating its validity. After reviewing the presupposition and inconsistency problems of existing approaches, we analyze their origins in-depth, propose the argument scheme-based approach, demonstrate its validity, and discuss its advantages and challenges. Finally, we argue that our approach, rather than diminishing the concept of argument structure, restores it to its rightful theoretical position.